Mathematical Modeling of Drying Behavior of Carrot Slices in a Cabinet Dryer - Shrestha, Rojee; Dhungel, Abhitosh; Dhakal, Santosh (Tribhuvan University Journal of Food Science and Technology, 2023)
Abstract available with the full text.